(untitled) (Conferencea, 2023)
The formation and development of the system of information provision of education by our government, the reform of the system of higher education institutions in accordance with the requirements of the "National Personnel Training Program", the creation and introduction of appropriate state education standards in this regard, educational institutions are necessary A number of things are being done, such as attracting scientists and highly qualified specialists to provide textbooks and literature, training and improving the qualifications of pedagogues in leading educational institutions in developed countries. Among these, issues of increasing the efficiency of teaching "Informatics and information technologies" and improving educational and methodological support in the training of programmers in technical educational institutions are also included.